Optical coherence tomography in varying aetiologies of renal artery stenosis: a case series. Issue 2 (13th May 2019) - Vijayvergiya, Rajesh; Kanabar, Kewal; Krishnappa, Darshan; Kasinadhuni, Ganesh; Sharma, Ashish; Akasaka, Takashi
Abstract: Background: Renal artery stenosis (RAS) is a common cause of secondary hypertension. The most common aetiology is atherosclerosis; however, other causes like fibromuscular dysplasia (FMD) and Takayasu arteritis (TA) are also frequently encountered. The lesion characteristics and its response to percutaneous intervention depend upon the aetiology of RAS. Optical coherence tomography (OCT) is an excellent imaging modality to analyse coronary lesions during percutaneous coronary interventions. The data regarding the utility of OCT in renal artery imaging is limited, consisting of a few case reports. Case summary: We hereby report four cases of RAS, each of different aetiology (atherosclerotic, FMD, post-transplant, and TA), who underwent OCT imaging of the renal artery along with percutaneous renal angioplasty. Discussion: The advantages of OCT imaging include demonstration of the arterial wall, pathological features of the disease, and to guide percutaneous interventions. The major limitation of OCT is its lower imaging depth, which may render imaging of large vessels difficult.